2023
DOI: 10.3390/insects14120912
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Fungal Pathogens Infecting the Invasive Spotted Lanternfly, Lycorma delicatula

Ann E. Hajek,
Thomas A. Everest,
Eric H. Clifton

Abstract: In the eastern United States, populations of the invasive spotted lanternfly, Lycorma delicatula, are abundant and spreading. Four species of naturally occurring entomopathogenic fungi have previously been reported as infecting these planthoppers, with two of these causing epizootics. Nymphal- and adult-stage lanternflies in Pennsylvania and New York were surveyed for entomopathogenic fungal infections from October 2021 to November 2023, and assays were conducted to confirm the pathogenicity of species that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
1
1
0
Order By: Relevance
“…Mycosed cadavers play a key role in regulating the pest population by producing conidia, which may cause secondary infection and increase the persistence of the pathogen for a longer period [73]. We observed that some cadavers did not show any fungal outgrowth, which was similar to the studies by [74] in which no fungal outgrowth on the surface of Lycorma delicatula (White) (Hemiptera: Fulgoridae) living insects was observed and rarely from cadavers; however, the growth appeared when incubated under humid conditions in the laboratory. Due to their concealed nature, and suitable humid condition inside the palm tree, mycosed cadavers may play a significant role for secondary infection of R. ferrugineus.…”
Section: Discussionsupporting
confidence: 88%
“…Mycosed cadavers play a key role in regulating the pest population by producing conidia, which may cause secondary infection and increase the persistence of the pathogen for a longer period [73]. We observed that some cadavers did not show any fungal outgrowth, which was similar to the studies by [74] in which no fungal outgrowth on the surface of Lycorma delicatula (White) (Hemiptera: Fulgoridae) living insects was observed and rarely from cadavers; however, the growth appeared when incubated under humid conditions in the laboratory. Due to their concealed nature, and suitable humid condition inside the palm tree, mycosed cadavers may play a significant role for secondary infection of R. ferrugineus.…”
Section: Discussionsupporting
confidence: 88%
“…Beauveria bassiana can suppress Spodoptera litura larvae up to 95% (Trizelia et al 2017;Afandhi et al 2020) and Nezara viridula up to 66.67% (Permadi et al 2019), reaching 100% 5 days after application (Siahaan et al 2021). Beauveria bassiana reduced 48% of Lycorma delicatula nymphs formed after 14 days of application (Hajek et al 2023). Beauveria bassiana can also control BPH, with mortality reaching 85-95% at a density of 10 8 -10 9 conidia (Ihsan et al 2023).…”
Section: Introductionmentioning
confidence: 99%